Conceptualization of Crypto Asset As A Collateral Object In Indonesian Positive Law - Firda Shafira; Hanif Nur Widhiyanti; Stephanie Wilamarta (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
The development of digital technology has given rise to crypto assets as a new form of digital wealth with economic value and can be legally traded in Indonesia, based on Bappebti regulations. However, their legal status as fiduciary collateral remains controversial because Indonesian property law does not fully accommodate intangible assets such as crypto assets. This study aims to analyze the feasibility of crypto assets as fiduciary collateral from the perspective of Indonesian positive law, using normative juridical research methods through legislative and conceptual approaches. The results show that functionally, crypto assets fulfill the characteristics of objects in collateral law, as they have economic value, can be legally transferred, and can be used as a basis for debt repayment. However, the lack of a mechanism for registration, assessment, and execution of digital collateral creates legal uncertainty in financing practices. Comparisons with other countries such as Switzerland, the United States, and Singapore indicate that the successful recognition of crypto assets as collateral depends heavily on a clear legal framework governing ownership protection and oversight mechanisms. In the Indonesian context, Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK) provides an opportunity for reform by expanding the authority of the Financial Services Authority (OJK) in regulating digital financial assets. Therefore, harmonization of the Civil Code, the Fiduciary Guarantee Law, the P2SK Law, and Bappebti regulations is necessary to ensure that crypto assets can be legally and effectively accommodated as collateral. With appropriate regulations, national law will be able to adapt to digital innovation without sacrificing the principles of legal certainty, justice, and expediency.